Regulation, asset complexity, and the informativeness of credit ratings - Jankowitsch, Rainer (2022)
We show that the effect of regulation on credit rating informativeness depends on asset complexity. Using the Dodd-Frank Act as a shock to the rating industry, we analyze the impact of rating changes on market prices, conditioning on various measures of complexity. Rating informativeness improves after Dodd-Frank, but not for assets with high complexity. Our results are robust to alternative measures of informativeness and provide strong evidence that the impact of regulation varies in the cross-section of securities. Our findings are consistent with models combining rating shopping with rating agencies that strategically decide on information acquisition and rating inflation.